The real James Bond a true story of identity theft, avian intrigue & Ian Fleming - Wright, Jim 1950- (Schiffer Publishing, 2020)
An illustrated biography of the ornithologist James Bond, the author of the book Birds of the West Indies and the namesake of Ian Fleming's fictional British spy